PENGARUH DAUR PETIK TERHADAP HASIL DAN MUTU PUCUK TANAMAN TEH (Camelia sinensis (L ) O. Kuntze) PRODUKTIF KLON TRI 2024 DAN DIAGAMMA - Dendi Restiandi; , Sudradjaf (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1998)
The experiment was conducted at Gedeh Plantation, PT Perkebunan Nusantara VII, Cianjur from January, 15th to March 25th on 1997, with the object was to evaluate the effect of plucking cycle on the yield and quality of TRI 2024 and Diagamma clones. The experiment was arranged in split plot design, shoot as the main plots were two clones of TRI 2024 (K1) and Diagamma (K2), and the sub plots were of levels plucking cycle : 0 (D1), 6 (D2), and 9 (D3) days. The result showed that 0 day plucking cycle has the highest shoot quality, as indicated by cumulative number of shoot and shoot analysis. Diagamma clone showed better shoot quality than TRI 2024 clone. The highest shoot quality was obtained from 0 day plucking cycle on Diagamma clone.